Nghiên cứu tổng hợp một số dẫn xuất 1,4-dihydropyridin dự đoán có hoạt chất sinh học - Châu, Phan Đình; Tuấn, Trương Quang; Tuyết Trinh, Nguyễn Thị; Khoa, Lê; Phương Dung, Phan Thị (Vietnam Journal of Chemistry, 2014)
The some products of 1,4-dihydropyridine 3a-f, 4 were prepared by the Hanzstch reaction between oxo compounds 1a-g with methyl acetoacetate. The obtained products 3a-f, 4 were confirmed by spectroscopic evidence.